Using lexical chunks to support grade 12th students in learning to speak English – A study at Vu Tien High School of Thai Binh = Sử dụng cụm từ vựng để hỗ trợ học sinh lớp 12 học nói tiếng Anh – Nghiên cứu tại trường THPT Vũ Tiên, Thái Bình. M.A Thesis Li - Bùi, Thị Thanh (University of Languages and International Studies, 2017)
43 p. + CD-ROM